Narrativas en Torno al Proyecto de Vida y Resiliencia de un Grupo de Mujeres que Fueron Maltratadas Por su Ex Pareja en la Ciudad De Bogotá D.C. (2018)
The purpose of this research project is to make known the narratives elaborated by a group of women, regarding the impact of their life project due to the aggressions of their ex-partner and their ability to resilience to get out of the adverse situation. It was developed through the type of qualitative research, with the participation of eight women residents of the city of Bogotá D.C. In addition, there was an instrument known as a data collection interview (EDRD), which contained 21 questions, which were interpreted through an analysis that responded to the objectives proposed at the beginning of the investigation. The answers of each of the participants were collected through a semi-structured interview, which was narrated by each of them, allowing to identify the types of violence to which they were exposed, the reorientation of their life projects, as well as the strategies elaborated and developed that allowed to overcome the episodes of aggression, the previous thing developed by means of an approach of investigation of qualitative type, possessing a narrative design of investigation.